APLIKASI INDEKS BIOKIMIA DALAM PENENTUAN KARAKTERISTIK DAN KESUBURAN TANAH YANG DIBERI BAHAN ORGANIK TERINKUBASI - Muhammad Basir-cyio (Universitas Tadulako, 2004)
The research aims to know the effectiveness of organic matter to soil chemistry and fertility, based on the Biochemical Index value. Two factors tested, were Organic Matter consisted of five levels, that is Bo = without organic matter, B1 = 5 t, B2 = 10 t, B3 = 15 t, and B4 = 20 t ha-1, and time incubation period consisted of two treatments (I-1 = 2 week and I-2 = 4 week). This research used the Completely Random Design (CRD) and the collected data were analysed using analysis of variance and Duncan’s Multiple Range Test at a significant level of 0.05. The results indicated that the organic matter improved some chemistry characteristics of Entisol of Palu Valey. Organic Matter Dose 20 t ha-1 was very effective to neutralize the degree of acidity with the improvement of pH-H2O till 7,45 and pH-KCl 6,57, include P-total and P-available of 32,97 me/100g and 23,91 ppm respectively. Organic matter 20 t ha-1 was effective to improve both the C-Organik till 4,0 g kg-1 (0,40%), and N-Total equal to 0,72 g kg-1 (0,072%), but the dose 20 t ha-1 was unable to improve the values of Biochemical Soil Fertility Index.Key words : Biochemical index, soil characteristics, and organic matter.